2020
DOI: 10.4103/ijpvm.ijpvm_277_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection and children: A comprehensive review

Abstract: Nowadays, COVID-19 is in pandemic stage, and concerns about the infection of children are on the rise. At first, it has been believed that children are not at risk while some evidences have shown that the risk of infection is lower in children than adults. The COVID-19 children indicated milder symptoms including cough, fever, sore throat, myalgia sneezing, and fatigue than COVID-19 adults. Lymphopenia, which is prevalent in adult cases, has not been reported in pediatric patients. The COVID-19 can also occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Moreover, people with underlying health conditions, which include diabetes, cardiovascular diseases, or most cancers, are at a higher risk of death than those without these health conditions. Recent studies have additionally suggested cases of COVID-19 infections in kids (Mehrabani, 2020 ). Notably, the general population tested for an additional occurrence of SARS-CoV-2 (0.15%) in comparison to CF patients (0.07%; Cosgriff et al, 2020 ).…”
Section: Epidemiological and Clinical Outcomes Of Sars-cov-2 In Cf Pa...mentioning
confidence: 99%
“…Moreover, people with underlying health conditions, which include diabetes, cardiovascular diseases, or most cancers, are at a higher risk of death than those without these health conditions. Recent studies have additionally suggested cases of COVID-19 infections in kids (Mehrabani, 2020 ). Notably, the general population tested for an additional occurrence of SARS-CoV-2 (0.15%) in comparison to CF patients (0.07%; Cosgriff et al, 2020 ).…”
Section: Epidemiological and Clinical Outcomes Of Sars-cov-2 In Cf Pa...mentioning
confidence: 99%
“…Symptoms in children will be milder, including cough, fever, sore throat, myalgia sneezing, and fatigue, but adults will be more severely affected. Lymphopenia may or may not be present and it seems to be less pronounced than in adults [ 85 , 86 ].…”
Section: Diagnosis and Testingmentioning
confidence: 99%
“…Results showed that the majority of COVID-19 deaths occurred with reduced oxygen saturation levels and elevated lactate dehydrogenase and erythrocyte sedimentation levels on admission in male elderly people [22]. Elevated amounts of C-reactive protein (CRP) reported in laboratory test results, which suggesting the infection by COVID-19 [23]. [24] stated that poor prognosis is associated with multiple laboratory features, including LDH and CPK.…”
Section: Biochemical Parameter Values Between Healthy Control Individ...mentioning
confidence: 99%